Effects of replacing timothy silage by red clover silage on environmental impacts, growth performance and carcass traits of finishing beef bulls - Huuskonen, Arto; Hietala, Sanna; Pesonen, Maiju; Manni, Katariina (Elsevier, 2025)
The objective of the study was to evaluate the effects of replacing timothy grass silage (GS) by red clover silage (RS) on environmental impacts, growth performance and carcass traits of finishing beef bulls. Total mixed rations (TMR) based on GS, RS and mixture of GS and RS (1:1 on dry matter (DM) basis; GRS) were fed ad libitum to sixty bulls. The proportion (g/kg DM) of the silages in the TMRs were as follows: (1) GS (600); (2) RS (600); (3) GS (300) and RS (300). Concentrate proportion was 400 g/kg DM with all treatments. Environmental impacts of the treatments were estimated using life cycle assessment approach with the following key impact categories: climate change, eutrophication, and acidification potential. As the red clover-grass modelling was acknowledged to have most uncertainty, it was completed with different scenarios of clover cultivation. Replacing GS by RS did not affect DM intake, gain, carcass weight or carcass conformation of the bulls. Carcass fat score of the bulls decreased with increasing RS proportion. As an average of the calculated scenarios the climate change impact was 17.8, 15.9, and 15.8 kg CO2 equivalents/kg of produced carcass, eutrophic emissions 18.6, 15.0, and 9.9 g phosphate equivalents/kg of produced carcass and acidifying emissions 38, 35, and 35 g acid equivalents/kg of produced carcass for GS, GRS, and RS, respectively. It can be concluded that replacing GS partially or completely with RS reduced environmental impacts (climate change impact, eutrophic emissions, acidifying emissions) per kg of produced carcass.
Keywords: sonnit; ruokinta; puna-apila; säilörehu; ympäristövaikutukset; beef production; Trifolium pratense; Phleum pratense; greenhouse gas emissions; eutrophication potential; acidification potential; modelling